Aberrant MRP14 expression in thyroid follicular cells mediates chemokine secretion through the IL-1β/MAPK pathway in Hashimoto's thyroiditis. Issue 6 (June 2018) - Luo, Xuan; Zheng, Tingting; Mao, Chaoming; Dong, Xin; Mou, Xiao; Xu, Chengcheng; Lu, Qingyan; Liu, Baocui; Wang, Shengjun; Xiao, Yichuan
Abstract : Myeloid-related protein 14 (MRP14) is responsible for inflammatory reactions. However, the correlation between MRP14 and Hashimoto's thyroiditis (HT) is still not clear. In this study, we examined the status of MRP14 in thyroid tissues and sera of HT patients and explored the mechanism of IL-1β-mediated regulation of MRP14 expression, as well as the effects of MRP14 on pro-inflammatory chemokine secretion in thyroid follicular cells (TFCs), to elucidate the role of MRP14 in HT development. Our results showed dramatically increased MRP14 expression in thyroid tissues and sera from HT patients. In addition, IL-1β significantly promoted the expression of MRP14 in TFCs, which was mediated by activation of the MAPK/NF-κB signalling pathway. More importantly, IL-1β induced the secretion of the chemokines GRO-2, CXCL9 and CCL22, which was dependent on the regulation of MRP14 in TFCs. Therefore, these findings suggested that under pro-inflammatory conditions, TFCs secreted chemokines with the help of MRP14 regulation, which might suggest a potential pathological mechanism of lymphocyte infiltration into the thyroid gland in HT.